2017
DOI: 10.1073/pnas.1617666114
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem-based management and the wealth of ecosystems

Abstract: We merge inclusive wealth theory with ecosystem-based management (EBM) to address two challenges in the science of sustainable management of ecosystems. First, we generalize natural capital theory to approximate realized shadow prices for multiple interacting natural capital stocks (species) making up an ecosystem. These prices enable ecosystem components to be better included in wealth-based sustainability measures. We show that ecosystems are best envisioned as portfolios of assets, where the portfolio's per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 45 publications
(55 reference statements)
0
24
0
Order By: Relevance
“…Many of the 'how' questions have been asked and answered in the literature already. For example, in a case where the boundary issues were relatively easy to resolve, Yun et al 40 showed how ecosystem-based management increases the wealth stored in Baltic Sea fisheries by about 30%. A regular production of accounts, rather than one-offs, will provide the necessary information to learn from past decisions.…”
Section: Determining What Is In Scopementioning
confidence: 99%
“…Many of the 'how' questions have been asked and answered in the literature already. For example, in a case where the boundary issues were relatively easy to resolve, Yun et al 40 showed how ecosystem-based management increases the wealth stored in Baltic Sea fisheries by about 30%. A regular production of accounts, rather than one-offs, will provide the necessary information to learn from past decisions.…”
Section: Determining What Is In Scopementioning
confidence: 99%
“…Such dynamics determine how the quantity of stock influences future benefits through changes in the stock itself and through its influence on human behavior. Thus, accurate natural capital and social valuation must consider the interdependent ecological relationships and dynamics that underlie and sustain natural resource production (Yun et al 2017). For instance, extractable timber, arising from the survival and production of forest trees, depends on fertile soils that are produced and maintained by soil organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging asset valuation frameworks now explicitly address species interdependence and ecological contingency (Quass et al 2013, Strong and Bond 2017, Yun et al 2017, Fenichel et al 2018). These frameworks can provide asset prices for populating sustainability metrics such as comprehensive or inclusive wealth accounts (Matson et al 2016, Lange et al 2018, Managi and Kumar 2018).…”
Section: Introductionmentioning
confidence: 99%
“…If renewable natural capital regenerates sufficiently quickly, then sustainable development may be possible even at low levels of substitutability. However, renewal functions of different forms of natural capital are heterogeneous and uncertain (28). Second, substitutability is not constant over space and time.…”
Section: Introductionmentioning
confidence: 99%